Emoji & emoticon-related legal issues / Nor Azlina Mohd Noor and Ahmad Shamsul Abd Aziz - Mohd Noor, Nor Azlina; Abd Aziz, Ahmad Shamsul (Universiti Teknologi MARA, Kedah, 2021)
Emoji and emoticon are the most important inventions in the history of communication. During the early days, emoticon and emoji were perceived as an aid in communication by helping people to clarify the tone of online texts. Even though sometimes the meaning really does not matter, the meaning of emoji and emoticon themselves were highly subjective and promoted an ambiguity. Though ambiguous, emoji and emoticon do convey meaning and legal practitioners need to consider when they will be legally binding or conveying intentions. Hence, the intriguing focus of this article is exploring the challenges that will be posed of the legal fraternity on the method usage in constructing the meaning of the emoji and emoticon and the judicial responses in Malaysia. This article is a conceptual paper applying a doctrinal legal research method particularly via a library research. This article concludes that the legal fraternity especially Malaysian judiciaries need to equip themselves with the legal framework with regards to the emoji and emoticon. The legal statutory interpretation needs to be extended into a wider scope to incorporate the emoji and emoticon. Due to the overwhelming used of digital application using emoji and emoticon in media social, the legal dispute will be foreseeable in the near future.